Influence of patch load length on plate girders. Part II: Numerical research. (July 2019) - Kovacevic, S.; Markovic, N.; Sumarac, D.; Salatic, R.
Abstract: The companion paper Part I [1 ] deals with the experimental campaign of longitudinally stiffened plate girders subjected exclusively to patch loading. The current paper focuses on the numerical research and parametric study of the influence of patch load length and initial geometrical imperfections on the ultimate strength of longitudinally stiffened plate girders. In order to assess the patch load resistance, a geometrically and materially nonlinear finite element analysis has been performed. For a better verification with the experimental results, the finite element model includes the experimentally measured initial geometrical imperfections and material properties based on laboratory tests. The verification of the numerical model has been obtained through the comparison of the numerically and experimentally attained results for the ultimate loads and elastoplastic behavior of the girders. It has been shown that the numerical and experimental results are in perfect agreement, which enabled a fruitful background for parametric analysis, in which different initial geometrical imperfections have been used to ameliorate understandings about their influence on the ultimate strength under different patch load lengths. Conclusively, it may be stated that initial geometrical imperfections can play a decisive role, especially for longitudinally stiffened girders. Initial geometrical imperfections of stiffened girders that correspond to deformed shape at the collapse (collapse-affine imperfections), especially in the zone where the load is applied, will give the most unfavorable ultimate strengths. For the considered geometry in the present paper, the third buckling mode of longitudinally stiffened girders corresponds to the deformed shape and the lowest ultimate strengths are obtained. Highlights: Initial geometrical imperfections can play a decisive role for both longitudinally stiffened and unstiffened girders. Unfavorable initial geometrical imperfections correspond to deformed shape at the collapse. Increasing the patch load length increases the strengthening effect. The strengthening effect is highly influenced by the shape of initial geometrical imperfections and patch load length. The lowest patch load resistance of longitudinally stiffened girders is obtained for the third buckling mode.